Documenting the Dragon Gate in Antonio Gaudí’s Finca Güell in Barcelona - Fernando Vegas López-Manzanares; Camilla Mileto (Virtual Archaeology Review)
A restoration project on the Dragon Gate in Antonio Gaudí’s Finca Güell in Barcelona has been carried out by the authors, paving the way for study and reflection on the evolution of various metric surveys of the building. The loss of Gaudí’s original project plans in an arson attack has made it necessary to refer to specific metric surveys at different times in the building’s history. These surveys date from the 1960s, 70s and 80s, while more recent ones incorporate technology and greatly improve geometric accuracy. These recent examples include three-dimensional (3D) laser scanning, providing the individual context of the objectives proposed. However, in the course of this conservation project, the authors have seen fit to complement the surveys and rectified photographs carried out by specialist teams in recent years. Hidden details of the construction of the iron dragon have also been recorded. The resulting painstaking survey can be of great use in guaranteeing the conservation of the architectural object which is the dragon gate. Furthermore, the alphanumerical and constructive documentation of all its pieces and their unions with adjoining pieces has yielded over 2100 records. As well as supplementing the 3D detailed drawings, these items have aided the stratigraphical study of subsequent interventions in order to repair, relocate and replace the pieces from the dragon gate using variants of different types of union (rivets, bolts, screws). This text reflects both the methodology used and the results obtained from the study. It also showcases the geometric documentation and constructive and structural knowledge which have improved the approach to this magnificent architectural object.